Nexus among Green Energy Investment, World Oil Price, Monetary Policy and Business Performance: Evidence from Energy Companies on the Vietnamese Stock Exchange - Hoan, Nguyen Dinh (International Journal of Energy Economics and Policy, 2022)
The abhorent effect of GHG emissions effects pushes nations to consider effective policies and take initiatives accordingly inorder to maintain the surface temperature at steep level. Practitioners, Policymakers and other regulators in this regard are urging firms to behave in environmental friendly way through the increased usage of energy effeciency such as increasing renewable energy consumption and minimizing carbon emissions. By doing so, firms are now taking great interest in green business practices such as green energy investment so that they may contribute in improving energy effeciency and carbon performance. Hence, the present article intends to evalaute the effectiveness of green energy investment, world oil price and monetary policy on business performance. The sample chosen for the study is Vietnamese energy enterprises which are listed in stock exchange. The data was gathered from 45 firms covering the period of 2010-2021. The study used two methods; CUP-FM and CUP-BC to examine the association. Obtained results reveal that the chosen constrcuts share positive relation with business performance. At the end of the paper, suggestions are also given in the light of results which are useful for future researchers.